Hubungan Antara Pemanfaatan Sumber Belajar Digital dengan Hasil Belajar Mahasiswa PBSI Universitas Muhammadiyah Jember - M. Dwi Bintang Ramadhan; Audy Yourdiansyah Firdaus; Agus Milu Susetyo (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the digital transformation in education, which requires students to optimize technology-based learning resources to achieve maximum academic achievement. The primary focus of this research is to investigate the impact of digital platforms on student learning achievement in higher education. This study aims to describe the level of digital learning resource utilization by students of the Indonesian Language and Literature Education Study Program (PBSI) at the University of Muhammadiyah Jember and to analyze the significance of the relationship between the utilization of these learning resources and the learning outcomes achieved. The research method used is a quantitative correlational study with a sample of 25 students. The research instrument was a questionnaire that had been tested for validity and reliability using SPSS, where the test results showed a very strong level of reliability with a Cronbach's Alpha value of 0.920 for the digital learning resource utilization variable and 0.962 for the learning outcome variable. The research findings indicate that the level of digital learning resource utilization by students is in the very consistent and structured category. The results of the Pearson correlation test indicate a positive and highly significant relationship between the utilization of digital learning resources and student learning outcomes. This indicates that the more intensive and effective students are in utilizing digital learning resources, the higher the learning outcomes they tend to achieve. The implications of this research underscore the importance of providing adequate digital infrastructure and enhancing digital literacy for students and lecturers to create a learning ecosystem that is adaptable to current developments.